Estructura microfluídica para espectroscopía de impedancia de células humanas - Morales-Ballesteros, Maria José (Instituto Tecnológico de Costa Rica, 2016)
This master's project is part of a research project at Instituto Tecnológico de Costa Rica, aiming at confining cells in microfluidic devices to be subsequently analyzed by impedance spectroscopy. The problem of confining cells is an ideal case to be solved by means of microfluidics, as this allows working with micrometric dimensions. This thesis presents studies of different microfluidic structures for a functional design for confinement of a set of living cells. Simulations were carried out using COMSOL Multiphysics for the study of fluid dynamics and the cell behavior in response to the fluid flow. Different geometries and dimensions were simulated after defining parameters such as perfusion velocity, cell diameter, and culture medium density. The goal of this thesis is to design a microstructure that allows confining cells maintaining the perfusion velocity. The device comprises a fluid inlet and outlet. The fluid outlet is necessary due to the requirement of a constant flow for maintaining the cell culture.
Proyecto de Graduación (Maestría en Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2016.
Keywords: Simulaciones; Fluídos; Células; Espectroscopía